Gluttonously Discourse of the French Language as a Reflection of Russian-French Language Contacts: Phonetic-Graphic Aspect - A. V. Ageyeva; Y. V. Smakhtina (Научный диалог, 2018)
Russian lexical borrowings in the gluttonic discourse of the French language as a result of French-Russian language contacts are considered. The authors point out that, despite the close cultural ties that linked France and Russia for several centuries, the percentage of Russian words in the French language is negligible, some of them are still not subjected to any scrutiny of linguists, belongs puttanesca discourse, and this is the novelty of this work. The results of the comparative analysis of Russian prototypes and reciprocal borrowing in the French language are presented from the perspective of the phonetic-graphical accent and specifics of languages of different structures. On the material of French culinary sites the authors formed the base of Russian borrowings in the sphere of gastronomy and described in detail the processes of phonetic-graphic assimilation. A review is made of allomorphic and isomorphic characteristics of the contact languages at the phonemic and prosodic levels, which determine the choice of a particular model of assimilation in the language-receptor. The study presents the classification of formal phonetic-graphic modifications of lexical units in the process of language transfer and inclusion in the new paradigm. The prospects for further research are outlined.